Predictibility of Returns with Buyback Cash Flows - Rasoul Foroughfard (Asian Academy of Management Journal of Accounting and Finance, 2024)
This article re-evaluates return and cash flow predictability, extending beyond dividends to include repurchases and issuances cash flows. Employing total distribution in the Campbell-Schiller decomposition, I examine how prices respond to discount rate and cash flow growth changes. Contrary to conventional wisdom, the results indicate that while dividend yield predicts returns, distribution yield, encompassing all distributions, emerges as a more effective predictor of future cash flows. This challenge established literature, emphasising the significance of considering all cash flow components in asset pricing analyses.